Heat Stress Targeting Individual Organs Reveals the Central Role of Roots and Crowns in Rice Stress Responses - Prerostova, Sylva; Jarosova, Jana; Dobrev, Petre I.; Hluskova, Lucia; Motyka, Vaclav; Filepova, Roberta; Knirsch, Vojtech; Gaudinova, Alena; Kieber, Joseph; Vankova, Radomira (Frontiers in Plant Science, 2022)
Inter-organ communication and the heat stress (HS; 45°C, 6 h) responses of organs exposed and not directly exposed to HS were evaluated in rice (Oryza sativa) by comparing the impact of HS applied either to whole plants, or only to shoots or roots. Whole-plant HS reduced photosynthetic activity (Fv/Fm and QY_Lss), but this effect was alleviated by prior acclimation (37°C, 2 h). Dynamics of HSFA2d, HSP90.2, HSP90.3, and SIG5 expression revealed high protection of crowns and roots. Additionally, HSP26.2 was strongly expressed in leaves. Whole-plant HS increased levels of jasmonic acid (JA) and cytokinin cis-zeatin in leaves, while up-regulating auxin indole-3-acetic acid and down-regulating trans-zeatin in leaves and crowns. Ascorbate peroxidase activity and expression of alternative oxidases (AOX) increased in leaves and crowns. HS targeted to leaves elevated levels of JA in roots, cis-zeatin in crowns, and ascorbate peroxidase activity in crowns and roots. HS targeted to roots increased levels of abscisic acid and auxin in leaves and crowns, cis-zeatin in leaves, and JA in crowns, while reducing trans-zeatin levels. The weaker protection of leaves reflects the growth strategy of rice. HS treatment of individual organs induced changes in phytohormone levels and antioxidant enzyme activity in non-exposed organs, in order to enhance plant stress tolerance.